BALLAD GENRE IN KABARDIAN LITERATURE: GENESIS AND EVOLUTION - L. B. KHAVZHOKOVA; R. S. ATLASKIROVA (Кавказология)
The article is devoted to the study of the ballad genre in Kabardian literature: the features of its genesis and evolution are considered in the context of the general Adyge literary process. For the first time, the issues of the origin of the genre in national poetry are studied, the entire evolutionary path is traced, from the origins to the present. The specificity of mastering the genre by Kabardian authors is investigated, specific works are analyzed for compliance / non-compliance with its canons. The ballads of Z. Naloev, B. Utizhev, A. Orazaev, Kh. Kazharov, A. Bitsuev are subjected to a comprehensive, complex analysis, their content and structural-compositional features are revealed. The article uses a number of scientific methods, including the main ones - analysis, description, as well as comparative-historical and hermeneutic methods. The results obtained can be helpful in studying the history of the ballad genre in the Adyghe literature, more generally in the North Caucasian literature, as well as in compiling special courses and writing qualification and other types of research papers.